A method of establishing an instantaneous water level model for tide correction. (1st January 2019) - Guan, Minglei; Li, Qingquan; Zhu, Jiasong; Wang, Chisheng; Zhou, Li; Huang, Chenhu; Ding, Kai
Abstract: Tide correction is important in ship-board bathymetric data. Currently, most tide correction algorithms use a space-time interpolation method to regain the composite sea surface morphology. These interpolation algorithms are mostly based on geometric interpolation. However, when the tide stations are insufficient in the survey region, the spatial pattern of tide change may not comply with the geometric trend. Some of the algorithms use tide simulation to obtain a space-time astronomical tide model for tide correction in tide-station-insufficient regions, because the instantaneous water level changes are mainly caused by astronomical tides in normal conditions. However, in some cases, the instantaneous water level effect of the short-period stochastic meteorological factors results in short-term water level anomalies, which can be difficult to simulate using a tide simulation method. Thus, in this paper, an instantaneous water level model for tide correction in tide-station-insufficient regions is proposed. The model includes the simulation of astronomical tide and deviation-tidal components. We first simulate the astronomical tidal model using a two-dimensional MIKE21 Flow Model. Then, we propose a deviation correction method to mitigate the deviation-tidal components. Using the revised instantaneous water level model, we present the instantaneous tide correction (ITC) algorithm. Then, we compare the ITC algorithm with the two commonly used algorithms of Discrete Tidal Zoning and TCARI. The results show that the ITC algorithm is superior to the common algorithms in terms of accuracy and applicability with respect to a tide-station-insufficient survey region. Our conclusion is that ITC algorithm is a feasible tide correction algorithm when tide stations are not sufficiently measured. Highlights: Propose an instantaneous water level model for tide correction in tide-station-insufficient survey regions. Construct the astronomical tide model using the 2D MIKE21 Flow Model for the simulation. Propose a deviation correction method to mitigate the deviation-tidal components.